If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -3 = w + 48 Reorder the terms: -3 + 3w = w + 48 Reorder the terms: -3 + 3w = 48 + w Solving -3 + 3w = 48 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. -3 + 3w + -1w = 48 + w + -1w Combine like terms: 3w + -1w = 2w -3 + 2w = 48 + w + -1w Combine like terms: w + -1w = 0 -3 + 2w = 48 + 0 -3 + 2w = 48 Add '3' to each side of the equation. -3 + 3 + 2w = 48 + 3 Combine like terms: -3 + 3 = 0 0 + 2w = 48 + 3 2w = 48 + 3 Combine like terms: 48 + 3 = 51 2w = 51 Divide each side by '2'. w = 25.5 Simplifying w = 25.5
| 6y+18+37=10y+16 | | 9p+4(2+p)=-18 | | 8z-17+21z-42=20z-3 | | 6m-7-4m-16=-23 | | 7w+21-48=5w | | 7w-3w+4w=-15 | | w+y+y-38=y+40 | | x+2=3-x | | -2+b+50=19b+5+7 | | 12a+33=45 | | q-2*3+48=-3+2q+37 | | 7p=p+18 | | p=a+3b+c | | 17a-4*20-40=20-2a+50 | | 3b-15=b+25 | | 16+v+32=-7*16+17v | | 4w=w+48 | | 10+9l-23=l+3*10+37 | | 9a-4=5a+36 | | 3-4x=-7 | | 6a+5-37=a+6*5-17 | | 15f-8f+13=55 | | 3q+35=50 | | t-3*3+48=5*3+5t-5 | | 49*2=3a-10a | | 8u-3=7u | | 2z+5=z+49 | | 10+q-3=6*5 | | 4z-28=z+48 | | 3*16=-9+k | | 8y+25=12y-37 | | x+32+45=35x+41 |